Advancing Project Management Education: A Hybrid Experiential-Simulation Learning Approach through Competitive Business Challenges for Student Engagement and Professional Readiness - Ehsan Shareef Salih (Managere: Indonesian Journal of Educational Management, 2025)
This study examines how a hybrid experiential–simulation learning approach can strengthen project management education by connecting theoretical understanding with practical application in higher education settings. The study is grounded in the recurring challenge that project management instruction often emphasizes conceptual knowledge, while students struggle to apply project management processes in dynamic, uncertain situations. To address this issue, a mixed-methods design was employed, combining quantitative measurement of learning improvement with qualitative exploration of students’ experiences during a competitive simulation activity. The core learning intervention involved a competitive business challenge in which students managed real-time decision-making, resource allocation, teamwork coordination, and a profit reinvestment mechanism designed to create iterative learning cycles. Findings indicate consistent improvement across all PMBOK knowledge areas, accompanied by notable development in decision-making, problem-solving, and collaborative capabilities. Student reflections further revealed increased engagement and confidence, as well as the unexpected emergence of entrepreneurial awareness during the learning process. These results suggest that integrating experiential participation, competitive simulation, and structured reflection creates a learning environment that more closely resembles professional project practice. The study therefore shows that authentic, student-centered learning experiences can reduce the gap between academic instruction and workplace expectations, offering a practical instructional model for enhancing applied competence and professional readiness in project management education.